Two-Phase Equilibrium Conditions in Nanopores - Michael T. Rauter; Olav Galteland; Máté Erdős; Othonas A. Moultos; Thijs J. H. Vlugt; Sondre K. Schnell; Dick Bedeaux; Signe Kjelstrup (Nanomaterials, 2020)
It is known that thermodynamic properties of a system change upon confinement. To know how, is important for modelling of porous media. We propose to use Hill’s systematic thermodynamic analysis of confined systems to describe two-phase equilibrium in a nanopore. The integral pressure, as defined by the compression energy of a small volume, is then central. We show that the integral pressure is constant along a slit pore with a liquid and vapor in equilibrium, when Young and Young−Laplace’s laws apply. The integral pressure of a bulk fluid in a slit pore at mechanical equilibrium can be understood as the average tangential pressure inside the pore. The pressure at mechanical equilibrium, now named differential pressure, is the average of the trace of the mechanical pressure tensor divided by three as before. Using molecular dynamics simulations, we computed the integral and differential pressures, <semantics> <mover accent="true"> p ^ </mover> </semantics> and p, respectively, analysing the data with a growing-core methodology. The value of the bulk pressure was confirmed by Gibbs ensemble Monte Carlo simulations. The pressure difference times the volume, V, is the subdivision potential of Hill, <semantics> ( p - <mover accent="true"> p ^ </mover> ) V = ϵ </semantics> . The combined simulation results confirm that the integral pressure is constant along the pore, and that <semantics> ϵ / V </semantics> scales with the inverse pore width. This scaling law will be useful for prediction of thermodynamic properties of confined systems in more complicated geometries.